Allergic Rhinitis and Asthma: A Profile of Beta-defensins in Serum of Iraqi Patients - Ahmed, Marwa B.; Ad’hiah, Ali H. (Iraqi Journal of Science, 2022)
Human beta-defenses (hBDs) are antimicrobial peptides involved in innate immune protection, and their association with the risk of respiratory allergy has been proposed. Therefore, this study sought to evaluate this association in allergic rhinitis (AR) and asthma (AS) of Iraqi patients. A case-control study was conducted to investigate serum levels of hBD1, hBD2, hBD3, and hBD4 in 52 AR and 60 AS patients and 61 healthy controls (HC). The hBDs were determined using enzyme-linked immunosorbent assay kits. Results revealed that median levels of hBD1, hBD2, and hBD3 were significantly elevated in the serum of AR and AS patients compared with HC (p < 0.01). Levels of hBD4 were also elevated in AR and AS patients but the differences were not significant. The levels of hBDs showed no significant differences between AR and AS patients. Age, gender, symptoms, and disease duration of patients influenced some of these variations. Logistic regression analysis indicated that hBD3 was the most important marker associated with the risk of AR and AS, and the estimated Odds ratios were 25.31 (95% confidence interval: 2.97-215.78; p = 0.012) and 32.20 (95% confidence interval: 2.49-415.89; pc = 0.032), respectively. Receiver operating characteristic curve analysis revealed that hBD3 occupied a very good area under the curve in AR and AS (0.83 and 0.84, respectively). In conclusion, the role of hBDs in the pathogenesis of AR and AS was indicated. In this context, hBD3 was the most important, and its association with the risk of developing AR and AS was suggested.